Species Composition and Spatial Distribution of Dominant Trees in the Forest Ecotone of a Mountain Ecosystem, Northern Thailand: DOI: 10.32526/ennrj.17.3.2019.21 - Marod, Dokrak; Hermhuk, Sutheera; Sungkaew, Sarawood; Thinkampheang, Sathid; Kamyo, Torlarp; Nuipakdee, Wimonmart (Environment and Natural Resources Journal, 2019)
Plants’ ecological niches are important to study, particularly for applying the knowledge to restoration programs. This study clarified the relationships of tree species composition and spatial distribution to environmental factors in a mountain ecosystem. A 3 ha permanent plot was established across the forest ecotone at Doi Suthep-Pui National Park, Chiang Mai Province, Thailand. The spatial distributions of the 20 dominant tree species were analyzed using a generalized linear model (GLM) combined with geographic information system (GIS) techniques. High species diversity was found, including 165 species representing 118 genera and 59 families. Elevation strongly influenced tree distribution, which could be divided into three groups: low-altitude species in deciduous dipterocarp forest (DDF), high-altitude species in lower montane forest (LMF) and coexisting DDF and LMF species. The GLM analysis revealed that soil texture, which ranged from sandy to clayey, influenced tree distribution. The results suggest that restoration programs should select suitable species based on their niches.